Impact of Disease Evolution on Efficacy Outcomes From Larotrectinib in Patients With Locally Advanced or Metastatic Tropomyosin Receptor Kinase Fusion–Positive Solid Tumors. (2021) - Bokemeyer, Carsten; Vassal, Gilles; Italiano, Antoine; De La Cuesta, Esther; Hiemeyer, Florian; Fellous, Marc; Marian, Marisca
Abstract : PURPOSE: Neurotrophic tyrosine receptor kinase ( NTRK ) gene fusions encode oncogenic, chimeric tropomyosin receptor kinase (TRK) proteins. Larotrectinib, an approved TRK inhibitor, is efficacious in locally advanced or metastatic (adv/met) TRK fusion cancer. We evaluated the time from initial diagnosis to locally advanced or metastatic disease and to initiation of larotrectinib treatment as well as larotrectinib impact on disease course. MATERIALS AND METHODS: Patients were grouped by prior lines of therapy (0, 1-2, and ≥ 3) and pre-larotrectinib duration of adv/met disease (short [< 3.5 months], medium [3.5 to < 15.7 months], and long [≥ 15.7 months]). Overall response rate (ORR), duration of response (DOR), and progression-free survival were assessed. RESULTS: One hundred sixty-four patients were evaluated. The median time from initial diagnosis to development of locally adv/met stage was 2.1 months; the duration of pre-larotrectinib adv/met disease was 7.3 months (n = 153). In patients with 0, 1-2, and ≥ 3 prior lines of therapy, the median time from diagnosis to adv/met stage was 0.9, 1.2, and 9.4 months, and 1.5, 5.8, and 29.0 months from adv/met disease to larotrectinib initiation, respectively. Clinical outcomes were independent of line of therapy (ORR: 86%, 63%, and 80%, respectively; median DOR: 27.6, not reached, and 32.9 months), and similar across subgroups of short, medium, and long duration of pre-larotrectinib adv/met disease status (ORR: 88%, 65%, and 69%, respectively; median DOR: not reached, 27.6, and 32.9 months). CONCLUSION: The short time from initial diagnosis to adv/met stage before larotrectinib suggests that NTRK gene fusion does not generally have a positive prognostic value. Patients on larotrectinib had high, sustained ORR, independent of number of prior therapies or duration of adv/met disease, suggesting that the effect of TRK inhibition in molecularly selected patients is independent of prior treatments or disease course.